Strategi Penyediaan Fasilitas dalam Implementasi Hasil Needs Assessment untuk Peningkatan Mutu Lembaga Pendidikan Islam - Nur Melinda; Ahmad Salabi; Yahya MOF (MAN 4 Kota Pekanbaru, 2026)
This research aims to analyze strategies for planning, managing, and distributing facilities in the implementation of needs assessment results at Islamic educational institutions. The urgency of this research is based on a managerial phenomenon where assessment reports often become merely administrative documents without actual implementation, due to the institution's lack of supporting capacity. The method used is a literature review (library research), collecting data from various systematic sources such as reference books and scientific articles. The results show that utilizing assessment results requires the provision of facilities across four main domains: physical facilities, non-physical facilities, human resources, and financial resources. These categories of facilities serve as bridges to connect the gap between the current condition and the ideal state expected in madrasahs or pesantrens. The conclusion emphasizes that the success of implementing assessment results largely depends on integrating findings into the institution's strategic plans, optimizing Islamic philanthropic funds (ZISWAF), and applying transformational leadership to overcome financial challenges and resistance to change. With proper prioritization, facility provision can sustainably improve the quality of education.